STRATEGY OF MENGROVE TOURISM IN PANGLONG VILLAGE, BINTAN REGENCY - Indah Andesta; Hendrikus Andre; Liu Richard (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
Mangrove tourism in Panglong village is a nature attraction that has tourist attraction as sampan tribe in Panglong village. Nevertheless, tourist attraction of sampan tribe is not supporting with the tourism facilities such as attraction, accessibilities, amenities and ancillary services. The objective of this research to analyses strategi is needed in development mangrove tourism to support the Unique’s of tourism attraction in Panglong village. The method of this research is using qualitative to the key actors in mangrove tourism area. In addition, the observation technic also uses to support data for this research in Panglong village. The result of research show that in generally tourism components in the disadvantages mainly in the amenities and ancillary service. The main development to increase tourism attraction in mangrove tourism, Panglong Village has a strong human resource to storytelling about sampan tribe, culture, and society in the Panglong village. Furthermore, the development of amenities need to increase especially on restaurant, homestay etc.